2021
DOI: 10.1177/20503121211054995
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the global burden of hemorrhage: The global blood supply, deficits, and potential solutions

Abstract: There is a critical shortage of blood available for transfusion in many low- and middle-income countries. The consequences of this scarcity are dire, resulting in uncounted morbidity and mortality from trauma, obstetric hemorrhage, and pediatric anemias, among numerous other conditions. The process of collecting blood from a donor to administering it to a patient involves many facets from donor availability to blood processing to blood delivery. Each step faces particular challenges in low- and middle-income c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 76 publications
0
16
0
Order By: Relevance
“…Though this study was specific to Malawi, recent studies have identified similar challenges that impede availability and distribution of blood and blood products for lifesaving transfusions [ 33 , 34 ]. The findings presented here can thus be applied to similarly resource-limited settings and provide a framework for identifying context specific barriers and solutions to best address the needs of obstetric patients being treated within said system.…”
Section: Discussionmentioning
confidence: 99%
“…Though this study was specific to Malawi, recent studies have identified similar challenges that impede availability and distribution of blood and blood products for lifesaving transfusions [ 33 , 34 ]. The findings presented here can thus be applied to similarly resource-limited settings and provide a framework for identifying context specific barriers and solutions to best address the needs of obstetric patients being treated within said system.…”
Section: Discussionmentioning
confidence: 99%
“… 12 Hemorrhage is the primary cause of most of these fatalities, and blood transfusions might prevent it. 13 Also, Ethiopia is a country with 25%–40% of maternal death every year due to a shortage of enough blood supply from blood donors. 14 Even though Ethiopia has a population of over 100 million people, the availability of blood remains inadequate to meet the increased demand for blood and blood components.…”
Section: Introductionmentioning
confidence: 99%
“…Yet, the population of SSA experiences a significant burden of diseases that require transfusion, such as malaria and sickle cell disease, trauma and postpartum hemorrhage, neglected tropical diseases, dietary insufficiencies as well as chronic diseases of adulthood and malignancy. 2,3 In addition, peripartum hemorrhage is a significant source of mortality for young women in SSA. In 2015, there were an estimated 201,000 maternal deaths in SSA with a maternal mortality ratio of 546 per 100,000 livebirths, over 45 times higher than in the developed world.…”
Section: Introductionmentioning
confidence: 99%
“…The 46 countries in the WHO Africa region collected about 4% of the global blood donations but have 13% of the world's population with many countries below the WHO recommended number of donations per 1000 population. Yet, the population of SSA experiences a significant burden of diseases that require transfusion, such as malaria and sickle cell disease, trauma and postpartum hemorrhage, neglected tropical diseases, dietary insufficiencies as well as chronic diseases of adulthood and malignancy 2,3 . In addition, peripartum hemorrhage is a significant source of mortality for young women in SSA.…”
Section: Introductionmentioning
confidence: 99%